Role of central noradrenergic system on FSH secretion induced by excitatory Amino acids - S Shahabi (Babol University of Medical Sciences, 2001)
Objective: Excitatory amino acids (EAA) and noradrenaline are known as a neurotransmitter, which stimulate gonadotropin secretion in female and male animals. This study was designed to evaluate the involvement of central noradrenaline system on FSH secretion induced by EAA in adult rats. Methods: Rats were implanted with monolateral cannula through the LC-SC (Locus Coeruleus-Sub Coeruleus) by stereotaxy. Then saline or glutamate (2 mg/ml) was injected into the cannula. Blood samples were drawn just 10 min after injection and were prepared for IRMA (Immunoradiometric Assay). For investigating the involvement of LC-SC in noradrenergic system, DSP-4 was used as an injection bilaterally one week before glutamate. Findings: Microinjection of glutamate significantly increased the plasma level of FSH in comparison to saline in control group. Pretreatment with DSP-4 significantly decreased the plasma level of FSH before glutamate injection. Conclusion: The results indicated that LC-SC in adult rats is one of the major sites affected by EAAs on FSH secretion by noradrenergic neurons.